High-Temperature-Induced Defects in Tomato (Solanum lycopersicum) Anther and Pollen Development Are Associated with Reduced Expression of B-Class Floral Patterning Genes - Muller, F.; Xu, J. M.; Kristensen, L.; Wolters-Arts, M.; de Groot, P. F. M.; Jansma, S. Y.; Mariani, C.; Park, Sunghun; Rieu, I. (My University, 2017)
Sexual reproduction is a critical process in the life-cycle of plants and very sensitive to environmental perturbations. To better understand the effect of high temperature on plant reproduction, we cultivated tomato (Solanum lycopersicum) plants in continuous mild heat. Under this condition we observed a simultaneous reduction in pollen viability and appearance of anthers with pistil-like structures, while in a more thermotolerant genotype, both traits were improved. Ectopic expression of two pistil-specific genes, TRANSMITTING TISSUE SPECIFIC and TOMATO AGAMOUS LIKE11, in the anthers confirmed that the anthers had gained partial pistil identity. Concomitantly, expression of the B-class genes TOMATO APETALA3, TOMATO MADS BOX GENE6 (TM6) and LePISTILLATA was reduced in anthers under continuous mild heat. Plants in which TM6 was partially silenced reacted hypersensitively to temperature elevation with regard to the frequency of pistilloid anthers, pollen viability and pollen quantity. Taken together, these results suggest that high-temperature induced down-regulation of tomato B-class genes contributes to anther deformations and reduced male fertility. Improving our understanding of how temperature perturbs the molecular mechanisms of anther and pollen development will be important in the view of maintaining agricultural output under current climate changes.
Citation: Muller, F., Xu, J. M., Kristensen, L., Wolters-Arts, M., de Groot, P. F. M., Jansma, S. Y., . . . Rieu, I. (2016). High-Temperature-Induced Defects in Tomato (Solanum lycopersicum) Anther and Pollen Development Are Associated with Reduced Expression of B-Class Floral Patterning Genes. Plos One, 11(12), 14. doi:10.1371/journal.pone.0167614
Keywords: Mads-Box Genes; Programmed Cell-Death; Heat-Stress Response; Male-Sterility; Flower Development; Carbohydrate Concentration